2021
DOI: 10.3390/jcm10184041
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Microcirculation as a Target for Innovative Therapies in AKI

Abstract: Acute kidney injury (AKI) is a serious multifactorial conditions accompanied by the loss of function and damage. The renal microcirculation plays a crucial role in maintaining the kidney’s functional and structural integrity for oxygen and nutrient supply and waste product removal. However, alterations in microcirculation and oxygenation due to renal perfusion defects, hypoxia, renal tubular, and endothelial damage can result in AKI and the loss of renal function regardless of systemic hemodynamic changes. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 152 publications
0
11
0
Order By: Relevance
“…13 Kidney blood flow is mainly controlled by autoregulation influencing preglomerular resistance and intraglomerular capillary pressure, which ensures consistent glomerular perfusion at variable MAP at wide ranges. 14 Impaired kidney autoregulation incites glomerular and tubular injury and, thus, dysfunction that may be further augmented by PCAS. 14 Only a few studies have assessed kidney outcomes in relation to specific targets of blood pressure in patients with OHCA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…13 Kidney blood flow is mainly controlled by autoregulation influencing preglomerular resistance and intraglomerular capillary pressure, which ensures consistent glomerular perfusion at variable MAP at wide ranges. 14 Impaired kidney autoregulation incites glomerular and tubular injury and, thus, dysfunction that may be further augmented by PCAS. 14 Only a few studies have assessed kidney outcomes in relation to specific targets of blood pressure in patients with OHCA.…”
Section: Discussionmentioning
confidence: 99%
“…14 Impaired kidney autoregulation incites glomerular and tubular injury and, thus, dysfunction that may be further augmented by PCAS. 14 Only a few studies have assessed kidney outcomes in relation to specific targets of blood pressure in patients with OHCA. In a post hoc analysis of 851 patients from the TTM trial (Target Temperature Management After Cardiac Arrest), authors found decreasing MAP values to be associated with lower estimated glomerular filtration rate and increased need for CKRT during targeted temperature management therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The kidney receives 1/4 of the cardiac output, but the kidney itself is vulnerable to hypoxia [11,12]. Early studies suggested that the maintenance of renal function depended on renal perfusion with su cient renal blood ow, and renal underperfusion was considered the key to the occurrence of SA-AKI.…”
Section: Discussionmentioning
confidence: 99%